Musical performance: preliminary stage for research production (Revista da Tulha, 2021)
The article portrays the types of reasoning applied in the sciences and arts, how artistic research is carried out, what are its characteristics and objectives. With regard to research modalities in music and the way in which musical performers develop a preliminary stage of musical research capable of supporting more advanced research in the sector. The publications by Marconi & Lakatos, L. Santaella, among others, and the musical interpreters who report how they develop their performances are based on part of this article, a situation capable of supporting important research in this sub-area.